Comparative analysis of chloroplast genomes and phylogenetic relationships in the endemic Chinese bamboo Gelidocalamus (Bambusoideae) - Wang, Chengkun; Li, Yonglong; Yang, Guangyao; Zhang, Wengen; Guo, Chunce (Frontiers in Plant Science, 2024)
Introduction Gelidocalamus Wen is a small yet taxonomically challenging genus within the Arundinarieae tribe. Recent molecular studies have suggested it may not be monophyletic. However, limited species sampling and insufficient molecular marker information have resulted in poorly resolved phylogenetic relationships within this genus. Methods The complete chloroplast genomes covering all 16 species and one variant of Gelidocalamus were sequenced, and comparative analyses were conducted. Phylogenetic analyses were performed using different molecular markers, including chloroplast data, the nuclear ribosomal DNA (nrDNA) repeats region, and 29 mitochondrial protein-coding genes. Additionally, the divergence times of Gelidocalamus were estimated to reveal their evolutionary history. Results The plastomes of Gelidocalamus ranged in size from 139,500 bp to 139,801 bp, with a total of 137 identified genes, including 90 protein-coding genes, 39 tRNA genes, and 8 rRNA genes. The size of the nrDNA repeats ranged from 5,802 bp to 5,804 bp. Phylogenetic analysis based on chloroplast data revealed that Gelidocalamus is polyphyletic, with different subclades distributed within the IV and V clades. However, phylogenetic analysis based on nrDNA and mitochondrial genes did not effectively resolve the relationships within the genus. Discussion Comparative analysis of chloroplast genomes indicated that Gelidocalamus shares a high degree of similarity with closely related genera in terms of chloroplast genome collinearity, codon usage bias, and repetitive sequences. Divergence time estimation suggests that it is a relatively young group, with all members appearing successively over the past four million years. The complex phylogenetic patterns may arise from the rapid radiation of Arundinarieae. This study provides a preliminary foundation for further in-depth research on the phylogeny, genomic structural features, and divergence times of this genus.